Psychological aspects of the class teacher’s professional activities - L. A. Kochemasova; M. I. Zhuleva (Вестник университета)
The article is devoted to determining the need for the formation of a system of knowledge and skills in the field of psychology among students of a pedagogical university, among future classroom teachers, taking into account modern trends in education. The article presents the results of a psychological and pedagogical study conducted to identify the psychological climate of the class collective, in which 28 students of the 5th grade from the MOAU “SOSH No. 87” of Orenburg took part. The following methods were used in the course of the study: analysis and synthesis, questionnaire (survey), observation. The study revealed the need to form a system of knowledge and skills in the field of psychology in future teachers. The results obtained suggest that distance learning has a negative impact on the formation process of a class collective and prevents its cohesion, which indicates the need to study psychological disciplines at a pedagogical university. This work may be of interest to students of pedagogical colleges and universities, employees of educational organizations, since with the introduction of the distance learning format, the problem of establishing a favorable psychological climate in the classroom, which has not lost its relevance for a long time, has significantly become aggravated.